CRIMINAL OFFENCE DURING MARTIAL LAW IN UKRAINE: PECULIARITIES OF QUALIFICATION - Sasko , Olena; Shvedova , Hanna; Orobets , Kostiantyn; Ovcharenko , Ruslan; Ostapenko, Oleksandr (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
The introduction of martial law in Ukraine has fundamentally altered the conditions of criminal proceedings, exposing the urgent need to adapt national legislation to wartime realities. The rapid escalation of armed conflict has created legal challenges related to the qualification of criminal offenses, particularly those classified as war crimes, and raised concerns regarding compliance with international standards. The purpose of this study is to examine how martial law affects the qualification of criminal offenses and to identify the main problems in applying the relevant provisions of the Criminal Procedure Code of Ukraine. The analysis is based on national legal acts, amendments adopted after February 2022, and judicial practice concerning crimes against national security and war crimes. The study employs the PRISMA methodology for systematic literature selection and integrates analytical, synthetic, comparative, and thematic approaches to ensure comprehensive coverage of the subject. The results reveal a marked increase in crimes against national security, peace, and human rights during the period of martial law, with the official statistics indicating a growth of over 40% in registered offenses of this category compared to the pre-war period. Judicial practice consistently demonstrates persistent difficulties in applying provisions related to war crimes, including inconsistent interpretations of legal norms and delays in adjudication. The findings also highlight gaps in adapting criminal legislation to wartime conditions. In conclusion, the study offers a systematic examination of the characteristics of criminal qualification under martial law, confirming both quantitative increases in wartime offenses and significant legal inconsistencies that warrant further scholarly attention.JEL Classification Codes: K14, K33, K38.